2016
DOI: 10.4314/ujas.v16i1.7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of<i> in vitro </i>digestibility using slaughtered and fistulated cattle as sources of inoculum

Abstract: In vitro methods of feed evaluation utilise rumen liquour from fistulated cattle. Fistulated cattle are associated with high acquisition and maintenance costs in addition to its implications on animal welfare. An experiment was conducted to compare in-vitro dry matter (INVDMD) and organic matter (INVOMD) digestibility of four diets using two sources of inocula namely; (i) slaughtered cattle and (ii) fistulated steers. Four fistulated crossbred (Friesian × Ankole) steers were assembled and fed on four diets in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
1
0
1
Order By: Relevance
“…Quatro jarros foram utilizados e uma rodada de análises foi realizada. O fluido ruminal de bovino foi obtido no frigorifico Fribarreiras (Barreiras, Bahia, Brasil) no momento do abate, o qual é adequado para utilização nesta metodologia (BEYIHAYO et al, 2015). Foram coletados 5 litros de fluído, o qual foi depositado em uma garrafa térmica pré-aquecida, mantendo-se a temperatura de 39°C.…”
Section: Methodsunclassified
“…Quatro jarros foram utilizados e uma rodada de análises foi realizada. O fluido ruminal de bovino foi obtido no frigorifico Fribarreiras (Barreiras, Bahia, Brasil) no momento do abate, o qual é adequado para utilização nesta metodologia (BEYIHAYO et al, 2015). Foram coletados 5 litros de fluído, o qual foi depositado em uma garrafa térmica pré-aquecida, mantendo-se a temperatura de 39°C.…”
Section: Methodsunclassified
“…Rumen fluid was collected from slaughterhouse animals (rams) following the protocol of Fortina et al (2022) [49], with small modifications. It was decided to use rumen fluid collected from slaughterhouse animals, first, because a significant difference in in vitro digestibility has not been found when the fluid was obtained from slaughtered or fistulated ruminants [50], and, second, because this was a more ethically acceptable approach [51]. It was reported that it is possible to store the rumen fluid without significant quality changes by putting it in thermic bottles wrapped in a thermic bag, for a period of up to 300 min after collection [49].…”
Section: Determination Of Released Gas Emissions In Vitro Analysismentioning
confidence: 99%
“…A more ethically acceptable approach that reduces stress and alleviates the suffering of animals by avoiding an invasive procedure is the collection of RF at slaughtering [40]. Alba et al [41] verified, through the use of an AD II incubator, that the rumen inoculum obtained from slaughtered cattle can be used to replace the use of cannulated animals and that this approach is a viable alternative to digestibility analysis.…”
Section: Rumen Fluidmentioning
confidence: 99%